The nature of pandemics - Von Lubitz, Dag K. J. E.; Gibson, Candace (Boca Raton : CRC Press, 2023)
"The ongoing COVID-19 disater-and the universal realization of the unceasing threat of even worse pandemics in the future-has resulted in a wealth of books, scientific papers, and journalistic analyses on the politics, medicine, and human tragedy of recent events. The Nature of Pandemics is not an outcrop of COVID-19 publication frenzy. It was conceived in the period between the SARS and Ebola pandemics, intended to address the critical, but commonly overlooked issues, that limit our readiness, immediate recognition, and rapid response to pandemic outbreaks. The book is the first to look holistically at the nature of pandemics as a phenomenon, and the challenges of mounting an organized, concerted global response to a worldwide lethal bioevent. While the majority of healthcare professionals at national and international levels recognize the danger, the establishment of consistent and effective countermeasures in the form of a global anti-pandemic network is, at best, still sporadic and inconsistent. The need to react quickly, and unhesitatingly mobilize all needed resources-rather than embark on a slow, deliberative and politically safe approach-is probably the paramount obstacle to the effective containment of a pandemic disease. Chapters are written by internationally known and widely respected experts from the US, Canada, Europe, Africa, and South America. They represent a cross-section of professions, many with academic and medical prominence supported by their direct involvement at the very forefront of the war against pandemic outbreaks, several knowing the personal and operational challenges involved with counter-pandemic responses. All involved are active in their respective fields and offer practical, real-world expertise based on hands-on work at the "front lines," providing profound, first-hand knowledge and recommendations for best practices. The opinions, often highly personal and perhaps even controversial, are based as much on theoretical considerations as on their extensive personal and highly insightful experience. As such, The Nature of Pandemics offer a multifaceted insight into problems that, if ignored initially, come to mar all subsequent response and mitigation efforts. The approach is rigorously intellectual and, in a field that often evokes passions, is equally rigorously dispassionate. It has to be so: in the modern world of pandemics "past is the prologue." Coverage provides solutions in developing readiness and mobilizing response to the current pandemic, and future ones. Addressing, military and security issues, government roadblocks to response, mutual aid agreements, ethics, global health organizations and response agencies-and the harsh realities of potential mass fatalities-the book examines the myriad complexities of pandemics and the real threat outbreaks"--
Politics, Economics, and Egos: When Agendas Conflict-A West African Case Study / John Jordan -- The Socioeconomic and Security Challenges in Responding to Medical Emergencies -- Pandemics or Disasters -- in Post-Conflict Society: The Liberian Ebola and COVID-19 Pandemic Experiences / Saint Jerome Larbelee -- Pandemics: Nature of an Emerging Global Threat -- Preparedness in the African Context / Doudou Fall -- Predicting mosquito-borne epidemics in Latin America / Jaime R. Torres -- The PREDICT Project: a Transdisciplinary Case Study in Partnerships for Pandemic Prevention and Preparedness / David J. Wolking and Jonna A.K. Mazet -- An Administrator's Nightmare / Steven D. Berkshire and Asa B. Wilson -- The Cascading Impact of Infectious Diseases on the Healthcare System / Amesh A. Adalja -- Supply Chain Infrastructure in Global Health Systems: A Strategic Asset for Pandemic Preparedness / Anne Snowdon -- Emerging Infectious Disease Communication Strategies of Health Organizations: An Internal and External View / Anat Gesser-Edelsburg -- From Woe to Go -- Understanding Rumours and their Role in Preparedness and Readiness for Pandemics / Judith Molka-Danielsen and Susan Balandin -- An Exploration of the Lived Experience of African Journalists during the 2014 Ebola Crisis / Anne Edimo, Blanche Morel, and David M. Secko -- Coordination of Global Efforts in Combatting Infectious Disease / Danny Sheath, Nefti-Eboni Bempong, and Antoine Flahault -- Health Information Technology and Infectious Disease: Learning from the Past / Stephanie H. Hoelscher and Dwayne Hoelscher -- Information Classification: General -- The Meaning of the Italian Fight against COVID-19: Protecting Fragile People and Defending the Social Values of Universal Public Health and Voluntary Activities through National Digital Solutions / Francesco Gabbrielli and Luigi Bertinato -- Virtual Reality and Augmented Reality to fight effectively against pandemics / Simon Richir, Abdelmajid Kadri, and Nicolas Ribeyre -- Biosecurity and the Police / John P. Sullivan -- The Impact of Pandemics on National and International Security / Stephen G. Waller -- Quarantine: A brief History of Infectious Pandemic Diseases in Canada / Candace J Gibson
Keywords: Pandemics -- History; Communicable diseases -- History; World health -- Diseases -- History; Epidemiology -- Political aspects; SOCIAL SCIENCE / Disasters & Disaster Relief; MEDICAL / Infectious Diseases; MEDICAL / Public Health